2018
DOI: 10.3906/kim-1703-13
|View full text |Cite
|
Sign up to set email alerts
|

Ligand binding constants of the cucurbit[7]uril predicted with molecular docking: a theoretical study

Abstract: A binding stability order predicting, molecular docking based fast technique was developed for host-guest complexes. Molecular descriptors were applied to ligand molecules to make the binding energy based docking scoring functions more efficient and reach the ± 0.50 log K unit theoretical precision for predictions. The goal of this work was to model complexes of cucurbit[7]uril (CB7) as a host molecule with different local anesthetics and choline and phosphonium choline molecules. The guest molecules were dock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A significant number of theoretical studies of supramolecular complexes in water have applied implicit solvation models. ,,,,,,,,, However, none of these studies treated dimerization processes. In a molecular dynamics study of cyclodextrin dimerization, it was found that explicit solvent models performed better than generalized Born models .…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of theoretical studies of supramolecular complexes in water have applied implicit solvation models. ,,,,,,,,, However, none of these studies treated dimerization processes. In a molecular dynamics study of cyclodextrin dimerization, it was found that explicit solvent models performed better than generalized Born models .…”
Section: Introductionmentioning
confidence: 99%